Tomato-made edible COVID-19 vaccine TOMAVAC induces neutralizing IgGs in the blood sera of mice and humans - Buriev, Zabardast T.; Shermatov, Shukhrat E.; Usmanov, Dilshod E.; Mirzakhmedov, Mukhammadjon K.; Ubaydullaeva, Khurshida A.; Kamburova, Venera S.; Rakhmanov, Bakhtiyor K.; Ayubov, Mirzakamol S.; Abdullaev, Adkham N.; Eshmurzaev, Jakhongir B.; Mamajonov, Behzod O.; Tulanov, Akmal A.; et al. (Frontiers in Nutrition, 2024)
Plant-based edible vaccines that provide two-layered protection against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outweigh the currently used parenteral type of vaccines, which predominantly cause a systemic immune response. Here, we engineered and selected a transgenic tomato genotype (TOMAVAC) that stably synthesized an antigenic S1 protein of SARS-COV-2. Twocourse spaced force-feeding of mice with ≈5.4 µg/ml TOMAVAC increased up to 16-fold synthesis of RBD-specific NAbs in blood serum and significant induction of S-IgA in intestinal lavage fluid. In a surrogate virus neutralization test, TOMAVAC-induced NAbs had 15-25% viral neutralizing activity. The results suggested early evidence of immunogenicity and protectivity of TOMAVAC against Coronavirus Disease 2019 (COVID-19) infection. Furthermore, we observed a positive trend of statistically significant 1.2-fold (average of +42.28 BAU/ml) weekly increase in NAbs in the volunteers' serum relative to the initial day. No severe side effects were observed, preliminarily supporting the safety of TOMAVAC. With the completion of future large-scale studies, highergeneration TOMAVAC should be a cost-effective, ecologically friendly, and widely applicable novelgeneration COVID-19 vaccine, providing two-layered protection against SARS-CoV-2.